ANALISA SIKAP DAN MINAT ANAK TERHADAP PENDIDIKAN SAINS PADA TINGKAT PENDIDIKAN DASAR - Dwi Prasetiyawati D.H.; Purwadi Purwadi (Universitas PGRI Semarang, 2015)
General purpose of this research is to develop attitudes and interest in science education,?é?á while the specific objectives of this research is to develop attitudes and interest in science education at the primary level. The method used in this study is a qualitative method. The main instrument in this study is the researcher, while supporting instrument used in this study were: 1) Polls or Questionnaires are a number of written questions used to obtain information from the respondents. In this study, a questionnaire used to determine the initial conditions for the study of the subject. 2) Observation Sheet is used by researchers at the time of observation activities. The conclusion that can be derived from this study are: 1). aspects - aspects that are used in the development of attitudes and interest in science education at the primary level in Surakarta used 7 aspects. 2). Attitude and interest in developing a science education at the primary level in the city of Surakarta using scala Likert scale range 1 -5, wherein each - each scale describe the characteristics of children in the attitude and interest toward science education.